CompTIA network+ certification exam guide : exam N10-006 - Meyers, Michael, 1961-; Computing Technology Industry Association (New York : McGraw Hill Education, 2015)
Mike Meyers, the #1 name in CompTIA training and exam preparation, is revising his bestselling exam guide to cover the 2015 release of the CompTIA Network+ exam. Electronic content includes a customizable test engine with 100+ practice exam questions, 20+ lab simulations covering the new performance-based items, video training, and more.
Includes index
Keywords: Computer networks -- Examinations -- Study guides; Electronic data processing personnel -- Certification; Telecommunications engineers -- Certification